2009
DOI: 10.1111/j.1365-2818.2009.03120.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy assessment of elastic strain measurement by EBSD

Abstract: Summary A detailed accuracy analysis of electron backscatter diffraction (EBSD) elastic strain measurement has been carried out using both simulated and experimental patterns. Strains are determined by measuring shifts between two EBSD patterns (one being the reference) over regions of interest (ROI) using an iterative cross‐correlation algorithm. An original minimization procedure over 20 regions of interests gives a unique solution for the eight independent components of the deviatoric displacement gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
90
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 13 publications
6
90
0
Order By: Relevance
“…The elastic strain contribution to the GND density is often not addressed experimentally, especially in the absence of a quantitative assessment of the significance of the elastic strain contribution to the dislocation density tensor. However, it is significant that in addition to lattice rotation field measurements, advances in the EBSD technique (Wilkinson et al, 2006;Villert et al, 2009;Kacher et al, 2009) have enabled the detection of surface elastic strain fields and the determination of the Kröner dislocation density tensor at surfaces (Wilkinson and Randman, 2010;Britton et al, 2013;Wilkinson et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The elastic strain contribution to the GND density is often not addressed experimentally, especially in the absence of a quantitative assessment of the significance of the elastic strain contribution to the dislocation density tensor. However, it is significant that in addition to lattice rotation field measurements, advances in the EBSD technique (Wilkinson et al, 2006;Villert et al, 2009;Kacher et al, 2009) have enabled the detection of surface elastic strain fields and the determination of the Kröner dislocation density tensor at surfaces (Wilkinson and Randman, 2010;Britton et al, 2013;Wilkinson et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Any error in pattern center calibration propagates into error in the shifts measured by the cross-correlations and results in erroneous measurements of elastic strain and orientation. Indeed, Villert et al have demonstrated that variation in pattern center parameters leads to artificial measurements and increased error [20]. The cross-correlation function is sensitive to sub pixel shifts in the ROIs.…”
Section: Pattern Center Calibrationmentioning
confidence: 98%
“…1), is of great importance in high resolution EBSD work, where the new techniques are much more sensitive to uncertainty in the microscope geometry than earlier EBSD methods. Error in pattern center introduces phantom strains and lattice rotations into absolute strain measurements [5,6]. It can also contribute to error in relative measures (such as deformation gradients) from pattern comparisons when the spatial translation between the compared patterns becomes too great.…”
mentioning
confidence: 99%